Evaluasi Realiasi Bijih Timah TB 1.42 PT Timah (Persero) Tbk Di Pemali Kabupaten Bangka: Evaluation Of Tin Ore Product Realization In TB 1.42 PT Timah (Persero) Tbk Of Pemali Bangka Regency - Epi, Epi; Mardiah, Mardiah; Irvani, Irvani (MINERAL, 2018)
TB 1.42 Pemaliwas managed PT Timah (Persero) Tbk. The mining system applied at TB 1.42 Pemali is a mechanical mining system where the mining system activities are conducted by transferring the excavation result of kaksa from work front to stockpile to be wasted using a jig. In terms of mining productivity, the realization of tin ore production was only 80% from the total production that has been planned by the company on November and Desember. Therefore, an evaluation of factors effecting prodution target is essential to do in order to meet unachieved production target. The research was conducted based on the performance coefficient value of load-haluage and transport equipment productivity in November and December assessed from the productivity of the excavators, loaders, and transforting vehicles in March, which is assumed to have the same condition as that in November adn December. An evaluation was conducted to examine the values of mine, effective usage of working time, and the number of bucket loading. The data is then processed using mechanical eatrhmoving formula.The value of performance coefficientin November and December were 0.9 and 0.8, while the performance coefficient of the company are 1.1 – 1.2. After conducting an evaluation, it is found that the factors that lead to failure in achieving the target of production are the long cycle time of the load-haulage equipment, low efficiency of labor, and low match factors. The efforts that should be taken to increase the realization of target achievement are decreasing the cycle time of the load-haulage, increasing the effective usage of working time, and addin in match factor. The cycle time is shortened to 1.159,5 seconds from the initial cycle time of 1.267,8 seconds. The effective usage of working time is increased to 0.75% from 0.727% and the number of load-haulage is increased to 6 from 4 units. After the changes have been done, the production realization in November and December increasing to 156.21 tons of Sn and 128.59 tons of Sn with performance coefficient value of 1.2, thus the production target of the company is achieved.